1988
DOI: 10.1159/000185145
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Hematuria

Abstract: A model of hematuria was established in rabbits. An accelerated form of unilateral Masugi nephritis was induced in 10 New Zealand white rabbits by an intravenous injection of duck antirabbit kidney serum and by ligating the left renal artery immediately after the injection of the antibody. All 10 rabbits became hematuric 1–2 weeks after the injection of the antibody and red blood cell (RBC) casts were found in the urinary sediment of all these animals. An ultrastructural examination of renal glomeruli by trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In the same man ner, we previously demonstrated linear defects in the basement membrane [11,12]. H o w e v e r, in the present case, we failed to observe gaps in the GBM by this proce dure.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In the same man ner, we previously demonstrated linear defects in the basement membrane [11,12]. H o w e v e r, in the present case, we failed to observe gaps in the GBM by this proce dure.…”
Section: Discussionsupporting
confidence: 69%
“…Bohle et al [6] demonstrated the escape of RBCs by scanning elec tron microscopy as well as by regular transmission elec tron microscopy in patients with mild mesangioproliferative glomerulonephritis. We also demonstrated the escape of RBCs from the rupture of the glomerular capillary wall by both transmission and scanning electron microscopy in animal models of hematuria [11,12], One characteristic of glomerular bleeding is the finding of dysmorphic RBCs in the urine. Several investigators [13,14] suggest that RBCs that originate in the glomeru lus are dysmorphic, whereas those that originate in other parts of the urinary tract are uniformly isomorphic.…”
Section: Discussionmentioning
confidence: 97%
“…We previously reported in Nephron that the hematuria observed in patients with glomerulonephritis was caused by a rupture of the glomerular basement membrane [1], a layer that had the strongest resistance to stretching among three layers within the cylindrical capillary wall, and had a three-dimensional meshwork structure composed of fine pores and fibrils and having an isotropic property [2, 3]. Using scanning electron microscopy, we noticed that the split lines caused by the ruptures of the glomerular basement membranes were almost always linear in shape and that they were frequently parallel to the axis of the capillary.…”
Section: Introductionmentioning
confidence: 99%